b) 3-2. {5 - 3 · [4 – (-2):(-1)]};
d) –52 +3 : [7 – (4):(-1)];
D 5 - [23 + (-7) - 2 - (1 - 6)];
h) (-2).(-4) – 32. [2-3(-4+6).
j) -(+4) - |12-81: (1-2 +51-1-11)
va rog ajutatima!!
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
b) 3−2(5−3(4−( −2 ): (- 1)) )
=3 −2* (5 −3*(4−2)) = 3 −2* (5−(3)* (2)) = 3−2*(5−6) = 3−(2*(−1)) = 3−(−2) = 5
d) −52+ 3 : (7 - (4 : -1) = -52 + 3 : ( 7- ( -4)) = -52 + 3 : 11 = - 569 / 11
D) 5−(23 +(−7)−2−(1−6)) = 5−(16−2−(1−6)) =5−(14−(1−6)) =5−(14−(−5)) =5−19 = - 14
h) (−2)*(−4)−32*(2−3*(−4+6)) = 8−32*(2−3*(−4+6)) =8−32*(2−(3)*(2)) =8−32(2−6)
=8−(32)*(−4) =8−(−128) = 136
j) −(+4)−(12 − 81 : ( 1 - 2 + 51 -1 -11) = - 4 - ( 12 - 81 : ( -1 + 51 - 1 -11) = - 4 - ( 12 - 81 : ( 50 - 1 -11) = - 4 - ( 12 - 81 / 38) = - 4 - 375 / 38 = - 527 / 38
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă